Politik Hukum Penanganan Sampah Plastik Sekali Pakai - Tanjung, Ni Putu Pranasari; Wiman Wibisana, Muhammad (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 1 (2020), 2020)
Bali Governor Regulation No. 97 of 2018 concerning Limitation of Disposal of Disposable Plastic Waste has an impact that makes the Bali Local Government a dilemma. This is quite reasonable considering that on one hand the Local Government of Bali should preserve the environment, so the human right to a healthy environment can be achieved. But on the other side, with the issuance of Bali Governor Regulation No. 97 of 2018 concerning Limitation of Disposable Plastic Waste Disposal has an impact on the reduced income earned by plastic bag manufacturers. This study aims to understand the objectives to be achieved with the issuance of Bali Governor Regulation No. 97 of 2018 concerning Limitation of Disposable Plastic Waste Disposal and to know the environmental costs as a solution to the pollution of disposable plastic waste. This research is a normative study using a statutory approach. In this study, the authors found that the basis for consideration of the Bali Governor's Regulation Number 97 of 2018 concerning Limitation of Disposable Plastic Waste Disposal is a manifestation of the provisions of Article 12 paragraph (3) and Article 13 paragraph (2) of the Bali Provincial Regulation Number 5 of 2011 concerning Management Rubbish. The policy was then concretized in the provisions of Article 2 of the Bali Governor Regulation No. 97 of 2018 concerning Restrictions on the Arising of Plastic Waste. The aim is to preserve the environment. Environmental costs can be applied as an alternative in handling disposable plastic waste. Through internalization of the environmental costs of plastic bag businesses, businesses can still sell plastic bags, however, the price of plastic bags is increased from the original price. The profits are not taken entirely by businesses, but go to the local treasury to be used by the Provincial Government of Bali for handling disposable plastic waste for environmental maintenance purposes. Peraturan Gubernur Bali Nomor 97 Tahun 2018 tentang Pembatasan Timbulan Sampah Plastik Sekali Pakai membawa dampak yang membuat Pemerintah Daerah Bali menjadi dilema. Hal ini cukup beralasan mengingat di satu sisi Pemerintah Daerah Bali memiliki kewajiban untuk menjaga kelestarian lingkungan, sehingga hak asasi terhadap lingkungan yang sehat dapat tercapai. Namun disisi lain, dengan dikeluarkannya Peraturan Gubernur Bali Nomor 97 Tahun 2018 tentang Pembatasan Timbulan Sampah Plastik Sekali Pakai membawa dampak terhadap berkurangnya pendapatan yang diperoleh oleh produsen kantong plastik.  Penelitian ini bertujuan untuk memahami tujuan yang hendak dicapai dengan dikeluarkannya Peraturan Gubernur Bali Nomor 97 Tahun 2018 tentang Pembatasan Timbulan Sampah Plastik Sekali Pakai serta mengetahui biaya lingkungan sebagai solusi terhadap pencemaran sampah plastik sekali pakai. Penelitian ini merupakan penelitian normatif dengan menggunakan pendekatan perundang-undangan. Dalam penelitian ini, penulis menemukan bahwa dasar pertimbangan Peraturan Gubernur Bali Nomor 97 Tahun 2018 tentang Pembatasan Timbulan Sampah Plastik Sekali Pakai merupakan pengejawantahan dari ketentuan Pasal 12 ayat (3) dan Pasal 13 ayat (2) Peraturan Daerah Provinsi Bali Nomor 5 tahun 2011 tentang Pengelolaan Sampah. Kebijakan tersebut kemudian dikonkretkan dalam ketentuan Pasal 2 Peraturan Gubernur Bali Nomor 97 Tahun 2018 tentang Pembatasan Timbulan Sampah Plastik. Tujuannya adalah menjaga kelestarian lingkungan. Biaya lingkungan dapat diterapkan sebagai alternatif dalam penanganan sampah plastik sekali pakai. Melalui internalisasi biaya lingkungan pelaku usaha kantong plastik tetap dapat menjual kantong plastik namun, harga kantong plastik dinaikkan dari harga semula. Keuntungannya tidak diambil seluruhnya oleh pelaku usaha, namun masuk ke kas daerah yang akan digunakan oleh Pemerintah Daerah Provinsi Bali untuk penanganan sampah plastik sekali pakai untuk tujuan pemeliharaan lingkungan.